The diagnostic value of fine needle aspiration biopsy and ultrasonography on thyroid nodule in Dr. Sardjito General Hospital, Yogyakarta - Wicaksono Probowoso Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
As the prevalence of thyroid cancer increases, a diagnostic method that can identify malignancy that warrants further surgical treatment is needed. Fine needle aspiration biopsy (FNAB) and ultrasonography (USG) are preoperative test for diagnosing thyroid tumor. This research aimed to calculate the diagnostic value of FNAB and USG on thyroid nodule patients in Dr. Sardjito General Hospital, Yogyakarta. This was a diagnostic test study using a retrospective designusing data from medical records of patients with thyroid nodules from January 2006 to December 2010. The diagnositic value of FNAB and USG including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy were calculated and compared with histopathological examination as the gold standard. Ninety medical records data of patients consisting of 71 females and 19 males who were diagnosed thyroid nodule with FNAB or USG before surgery were evaluated in this study. The results of FNAB of 90 patients were as follows: 54 (60.0%) benign, 6 (6.7%) malignant, and 30 (33.3%) follicular neoplasm. Meanwhile, the results USG of 90 patients were as follows: 38 (42.2%) benign, 15 (16.7%) malignant and 37 (41.1%) non determined. The diagnostic value of FNAB was described as follows: sensitivity of50.0%, specificity of 100%, PPV of 100%, NPV of 50.0% and an accuracy of 60.0%, whereas the diagnostic value of USG was described as follows: sensitivity of 81.8%, specificity of87.5%, PPV 60%, NPV 94.5% and accuracy of 50.0%. In conclusion, the diagnostic value of FNAB and USG in stablishing diagnosis of thyroid nodule is still low. The FNAB has higher accuracy compared to USG for diagnosing thyroid nodules.Keywords: diagnostic value - fine needle aspiration - ultrasonography - thyroid nodule - histopathological examination